Severe Neonatal Morbidity in Forceps versus Vacuum Birth among Individuals with Previous Cesarean Birth: A Population-Based Retrospective Cohort Study - Oltean, Irina I.; Kirubarajan, Abirami; Hébert, Vanessa; Darling, Elizabeth K.; D'Souza, Rohan; Muraca, Giulia M. (American Journal of Perinatology, 2025)
We sought to compare severe neonatal morbidity associated with forceps versus vacuum birth among individuals with prior cesarean birth.We conducted a population-based retrospective cohort study using data on all full term, singleton, cephalic vaginal births among individuals with prior cesarean birth in the United States (2014–2021). The exposure was operative vaginal birth (forceps vs. vacuum) and the primary outcome was composite severe neonatal morbidity, defined as assisted ventilation > 6 hours, neonatal seizures, and Apgar score < 4 at 5 minutes. We primarily compared the distribution of severe neonatal morbidity among operative vaginal births by instrument (forceps compared with vacuum) and fit multivariable logistic regression models to obtain adjusted odds ratios (AORs) and 95% confidence intervals (CIs) for severe neonatal morbidity in forceps versus vacuum births while accounting for confounders.The study population included 531,440 births. The rate of severe neonatal morbidity was 0.7% with spontaneous vaginal birth, 1.6% with forceps, and 1.3% with vacuum. Adjusted models showed higher rates of severe neonatal morbidity with forceps versus vacuum birth, but this association was not statistically significant (AOR: 1.20, 95% CI: 0.96, 1.50). Analysis of each component of the severe neonatal morbidity composite showed a 39% higher odds of assisted ventilation > 6 hours (AOR: 1.39, 95% CI: 1.07, 1.80) in forceps compared with vacuum births.Rates of severe neonatal morbidity are higher following operative versus spontaneous vaginal births with no difference based on type of instrument (forceps or vacuum). The choice between instrument should depend on the clinical situation, patient preference, and the experience, skill, and comfort of the operator.
Keywords: pregnancy; infant; newborn; vacuum extraction; obstetrical; obstetrical forceps; birth; obstetric; obstetrical surgical instruments; morbidity